EVALUATION OF THE PRIVATE PENSION SYSTEM IN TURKEY AS AN EXAMPLE OF BEHAVIORAL ECONOMICS - Kaya, Perihan Hazel; Tanış, Tevfik (PEOPLE: International Journal of Social Sciences, 2019)
Traditional economic theories largely suggest that the individual is in activities that make rational decisions and maximize their own benefits. But according to behavioral economics, people's decisions and choices are not always perfect. Human behavior is influenced by feelings like justice and equality and social, cultural and psychological events so that the individual gets away from the assumption of rationality. Behavioral economics examines how psychological factors can be used to benefit people. One of the best examples of behavioral economics practice today is the individual pension system. In this study of behavioral economics approach is evaluated within the private pension system in Turkey. Turkey has benefited from the solutions put forward in the application of behavioral economics at the private pension system steps have been taken towards this.